Pengaruh Komitmen dan Lingkungan kerja Terhadap Engagement Karyawan SMK YASBU Al-Qomariah TASIKMALAYA - Suci Putri Lestari; Arga Sutrisna (LP2M Universitas Perjuangan Tasikmalaya, 2019)
The purpose of this study is to find out the commitment and work environment will affect the engagement of YASBU Al-Qomariah Vocational employees. The research method used in this research is explanatory research. The use of this method is because the researcher does not only describe empirical facts found in the field, but also intends to analyze and explain the influence between variables. Data collection is obtained through interviews, questionnaires and literature studies. The population in this study were employees of YASBU Al-Qomariah Vocational High School. Methods Analysis of the data used is the Multiple Regression Analysis, where data is processed with the help of SPSS. The results of testing the data using the regression equation showed the results of a positive and significant effect of commitment to engagement variables with a significant value of 0.001 smaller than 0.05, while the work environment was not significant with a value of 0.563.Keywords: Commitment, work environment, employee engagement.